2023
DOI: 10.1021/acssuschemeng.3c04675
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Co3O4 Nanoparticle-Loaded Carbon Spheres for the Simultaneous Ultrasensitive Electrochemical Determination of Hydroquinone and Catechol

Qian-Qian Xu,
Qing-Qing Wang,
Zhong-Gang Liu
et al.

Abstract: Owing to their toxicity, highly sensitive detection of the two main dihydroxyphenyl isomers of hydroquinone (HQ) and catechol (CC) is of great significance for environmental monitoring. In this work, a novel strategy has been developed to prepare ultrafine Co3O4 nanoparticle-loaded carbon spheres (Co3O4/CSs) as high-performance electrochemical sensing materials for the simultaneous determination of HQ and CC. Ultrafine Co3O4 nanoparticles were formed and uniformly decorated on the surface of carbon spheres thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…12–15 Recent experimental and theoretical results showed that MnCo 2 O 4 catalyst demonstrated good redox properties, multiple valence states, outstanding mechanical robustness, higher intrinsic catalytic activity owing to larger catalytically active centers arising from the higher Co 3+ state, and modest binding proficiency towards the reactants (protons or atomic hydrogen and water molecules). 16–21 However, most of the reported processes can merely catalyze HER in alkaline or acidic media efficiently. 20,22 To boost the catalytic HER performance of MnCo 2 O 4 catalysts through the effective improvement of catalytic sites and conductivity for water dissociation by converting the catalyst into nitrides, phosphides, and/or sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…12–15 Recent experimental and theoretical results showed that MnCo 2 O 4 catalyst demonstrated good redox properties, multiple valence states, outstanding mechanical robustness, higher intrinsic catalytic activity owing to larger catalytically active centers arising from the higher Co 3+ state, and modest binding proficiency towards the reactants (protons or atomic hydrogen and water molecules). 16–21 However, most of the reported processes can merely catalyze HER in alkaline or acidic media efficiently. 20,22 To boost the catalytic HER performance of MnCo 2 O 4 catalysts through the effective improvement of catalytic sites and conductivity for water dissociation by converting the catalyst into nitrides, phosphides, and/or sulfides.…”
Section: Introductionmentioning
confidence: 99%